A SYSTEMATIC JOURNAL REVIEW: IDENTIFYING THE MOST COMMON SITE AND THE MOSTLY SHOWN CLINICAL MANIFESTATION OF BRAIN MENINGIOMA - Alya Tanti Nurjanah; Dina Qurratu Ainin; Dinmas Arif Almamfaluthi; I Gusti Ayu Diah Kusuma Wardani; Dini Wurnaning Budi; Made Bayu Sanjaya Sanjaya (LPPM Universitas Dhyana Pura, 2026)
Meningioma is the most common primary intracranial tumor, originating from the meninges surrounding the brain and spinal cord. Although its exact etiology remains unclear, exposure to ionizing radiation, hormonal factors, and genetic predisposition are considered important risk factors. This systematic review aimed to identify the most common anatomical location and clinical manifestations of brain meningioma worldwide. A literature search was conducted in PubMed, MedLine, and ProQuest for studies published between 2015 and May 2025. Eligible studies included original research focusing on intracranial meningioma, while studies involving other central nervous system tumors or non-journal publications were excluded. Of 95 identified articles, 10 studies involving more than 500 patients met the inclusion criteria. The findings consistently demonstrated that supratentorial meningiomas were the most frequent, particularly those located at the convexity (30%) and parasagittal region (24%). The most common clinical presentation was nonspecific headache, followed by vomiting, decreased level of consciousness, and other neurological deficits depending on tumor location. These findings highlight that supratentorial meningiomas represent the predominant anatomical site and that nonspecific headache remains the most frequent presenting symptom, emphasizing the importance of early clinical recognition and neuroimaging evaluation.